HISTORICAL FEATURES OF THE FORMATION OF THE NAQSHBANDI-MUJADDIDI ORDER (Western European Journal of Historical Events and Social Science, 2025)
The article describes the end of the 16th century and the beginning of the 17th century, which was marked as a new period in the development of the Naqshbandi order when the branch of the tariqah Naqshbandi-Mujaddidi emerged. Moreover, it has investigated the specific role of Ahmad Sirhindi Farooqi Rabbani (1564-1624), who lived in Sirhind, India in the late 16th and early 17th centuries, who was one of the theorists of the order and whose name is mentioned in a series of orders that are currently in use in our country.